Improving Contextualized Problem-Solving Skills among Grade 8 Students Through "Digestive System" Problem-Oriented Learning: A Study Intervention Findings in the Complex Domain - Alfanisa Dwi Pramudia Wardani; Wirawan Fadly; Juan David Martinez Zayas (Journal of Science Learning, 2024)
Indonesia needs more appropriate learning methods and educational policies to improve literacy and numeracy skills, including problem-solving competence. These two capabilities are fundamental in this era of Industrial Revolution 4.0. This research investigates whether Digestive System learning designed to be oriented toward contextual problems with direct SESD-based teaching encourages students' ability to solve contextual problems better than conventional learning in the classroom. Data collection included paper and pencil assessments of students' problem-solving skills through a quasi-experimental study using a pretest-posttest experiment control group design. The experimental group received learning about the digestive system based on the principles of education for sustainable development. The study sample comprised class VIII students at SMPN 4 Ponorogo. The result of this research shows that the ANCOVA analysis with pre-test scores as a covariate: F (6.860) indicates that the experimental group displayed more autonomy, independence, and openness in their approach to problem-solving due to the treatment they received. With a Cohen's d of 0.60, 72.4% of the "treatment" group will be above the mean of the "control" group (Cohen's U3), 76.6% of the two groups will overlap, and there is a 66.3% chance that a person picked at random from the experimental group will have a higher score than a person picked at random from the control group.